The relationship between unemployment,employment expectations and happiness in turkeyfor the years: 2003-2018 - DUMLUDAĞ, DEVRİM (My University, 2022)
This study analyses the relationship between employment/unemployment, expectations, and happiness in Turkey by using the Life Satisfaction Survey conducted regularly by the Turkish Statistical Institute (TUIK) since 2003. In the study, happiness of unemployed individuals comprising of different people between 2003-2018 have been analysed through a comparison of those in employment versus those outside of the workforce. In addition to the relationship between unemployment and happiness; the entire sample between the ages of 18-64 and the unemployed were compared in terms of their employment expectations for the following year for the country as well as their personal employment expectations and happiness. The results of the study indicate that being unemployed is correlated with negative life satisfaction, and there is a negative correlation with happiness and unemployment. As a result of the study, it is determined that there is a difference between those who live in the region with a high unemployment rate and those who live in the region with a low unemployment rate. Accordingly, the life satisfaction of an unemployed person living in an area with a high unemployment rate is less negatively affected than an unemployed person living in an area with a low unemployment rate.

Bu çalışma, Türkiye İstatistik Kurumu (TÜİK) tarafından 2003 yılından bu yana düzenli olarak yapılan Yaşam Memnuniyeti Anketi kullanılarak Türkiye’de istihdam/işsizlik, beklenti ve mutluluk arasındaki ilişkiyi analiz etmektedir. Çalışmada, 2003-2018 yılları arasında farklı kişilerden oluşan işsiz bireylerin mutlulukları, istihdamda olanlar ve işgücü dışında olan bireyler ile karşılaştırılarak analiz edilmiştir. İşsizlik – mutluluk ilişkisinin yanı sıra; 18-64 yaş örneklemin tamamı ile sadece işsizlerin gelecek yıl ülke ve kişisel çalışma beklentileri analiz edilmiştir.Çalışmanın sonuçları işsiz olmanın olumsuz yaşam memnuniyeti ile ilişkili olduğunu, mutluluk ve işsizlik ile negatif bir korelasyon olduğunu göstermektedir. İşsizlik oranının yüksek olduğu bölgelerde yaşayan işsizlerin görece daha az olumsuz etkilendiği, iş bulma konusunda hem birey bazında hem de ülke bazından gelecek yıla dair olumlu beklentiye sahip olmak mutlulukla pozitif korelasyona sahipken, olumsuz beklentilerin ise negatif korelasyona sahip olduğu gösterilmektedir
Keywords: Istihdam Beklentileri; Mutluluk; Öznel Iyi Oluş; Türkiye; Işsizlik; Employment Expectations; Happiness; Subjective Well-Being; Turkey; Unemployment